Dr. Ruth A. Parmelee and the Changing Roll of Near East Missionaries in Early Twentieth Century Turkey - Metaxas, Virginia (Role of the American Board in the World: Bicentennial Reflections on the Organization's Missionary Work, 1810-2010, 2012)
The American Board of Commissioners for Foreign Missions (ABCFM) was the country's first creator of overseas Christian missions. Founded in 1810 and supported by a coalition of Calvinist denominations, the ABCFM established the first American missions in India, China, Africa, Oceania, the Middle East, and many other places. It was America's largest missionary organization in the nineteenth century, and its influence was immense. Its missionaries established the first Western schools and hospitals in many parts of the world, and they successfully promoted women's rights and other ideals from the Enlightenment. They also transformed oral languages such as Zulu, Hawaiian, and Cherokee into written form, and they preserved many elements of premodern cultures (albeit not always intentionally). The contributors to this book provide valuable insights on the work of the ABCFM (which exists today under a different name). Some of the contributors profile the lives of notable ABCFM missionaries, others focus on ideological shifts within the Board, and still others chronicle the Board's role in historic events, including the Opium Wars, the colonization of Hawai'i, and the Armenian Genocide. From reading this book, people will come to understand why the ABCFM is widely viewed as America's most historically significant missionary organization.
Keywords: American Board of Commissioners for Foreign Missions; History; Congregational churches; Missions; Missions, American; dept.his; faculty_collection

Southern Medicine for Southern People Vietnamese Medicine in the Making - Monnais-Rousselot, Laurence; Thompson, Claudia Michele; Wahlberg, Ayo (Cambridge Scholars Pub., Cambridge Scholars Publishing, 2012)
What is a national medicine? What does it mean for a medicine to be traditional and scientific at the same time? How could a specifically Vietnamese medicine emerge out of the medical practices and treatments that have flourished and waned during key soci
Keywords: History; Traditional medicine; Vietnam; Vietnam; Traditional medicine; dept.his; faculty_collection

Ella Grasso: Connecticut's pioneering governor - Purmont, J.E. (Ella Grasso: Connecticut's Pioneering Governor, 2012)
When Ella Tambussi Grasso ran for governor of Connecticut in 1974, she had not lost an election since she was first voted into the state's General Assembly in 1952. The people of Connecticut chose her as the nation's first woman to be elected governor in her own right-the capstone of a long and successful career dedicated to public service, effective government, and the democratic process. During her tenure as governor, Grasso's leadership was tested in the face of fiscal problems, state layoffs, and budget shortfalls. The daughter of Italian immigrants, she endeared herself to her constituents during the great Blizzard of 1978, when she stayed at the State Armory around the clock to direct emergency operations and make frequent television appearances. Author Jon E. Purmont, who served as Grasso's executive assistant when she was governor, draws on his diary from that time, research in Grasso's archives, and interviews with Grasso's family and friends to give us a rich and intimate portrait of this political pioneer. © 2012 Jon E. Purmont. All rights reserved.
Keywords: dept.his

Would a saola by any other name still be a saola?: Appropriating rare animals, expropriating minority peoples - Thompson, C.M. (State, Society and the Market in Contemporary Vietnam: Property, Power and Values, 2012)
Keywords: dept.his